Unlocking Land Values to Finance Urban Infrastructure : Land-Based Financing Options for Cities - Peterson, George E. (World Bank, Washington, DC, 2012)
Raising capital to finance urban infrastructure is a challenge. One solution is to 'unlock' urban land values - such as by selling public lands to capture the gains in value created by investment in infrastructure projects. Land-based financing techniques are playing an increasingly important role in financing urban infrastructure in developing countries. They complement other capital financing approaches, such as local government borrowing, and can provide price signals that make the urban land market more efficient.